Identifying missing data mechanisms in (2 x 2)-contingency tables - Thomas Nittner; Helge Toutenburg (Ludwig-Maximilians-Universität München, Sonderforschungsbereich 386 - Statistische Analyse diskreter Strukturen, 2004)
Consider the sample of two binary variables X and Y with some missing structure within X or Y. The knowledge about the corresponding values of the observed covariate allows to play through all possible originally' complete data sets. After defining the notation, including some theoretical work, a test for non MCAR within the complete case table is presented. Simulating all possible tables enables some testing on non MAR. A simulation experiment is used to illustrate this context.
urn:nbn:de:bvb:19-epub-1744-7
Keywords: 519; missing data mechanism : odds-ratio; simulation experiment; testing non MAR